Comparison between Different Models for the Zn Adsorption in Some Calcareous Soils of Erbil Governate - Shayan I. Dizayee; Chnar H. Abdulrahman (Zanco Journal of Pure and Applied Sciences, 2023)
This study was investigated to evaluate Zn adsorption using some adsorption isotherms in calcareous soils in Erbil governorate. Soil samples were taken from twelve different agricultural sites Duplicate 1 gm of soil samples were adjusted at 298° K with 50 ml of 0.01 M CaCl2.7H2O solution containing a series of Zn concentrations (0, 2, 4, 8, 16, 32, and 64) mg kg-1 using ZnSO4.7H2O. In each soil sample the amount of Zn adsorbed was calculated by using Langmuir, Freundlich, Temkin, Dubinin-Radushkevich, and Harken-Juren isotherms. The results relieved that the Langmuir model was best fitted to the Zn adsorption in the studies soils, as it had the higher R2 and lowest S.E which were 0.923 and 0.002 at 298 ̊ K respectively. While the lowest value of R2 (0.749 at 298 °K) was recorded by Harken-Juren equation. Based on the results, the effectiveness of the models in description of Zn sorption were arranged as follow: Langmuir > Freundlich > Dubinin-Radushkevich > Temkin > Harken-Juren. The lowest binding energy and maximum adsorption was recorded by Langmuir model which was regarded as the best model.